Transitions in frequency of hookah smoking among youth and adults: findings from waves 1 and 2 of the Population Assessment of Tobacco and Health (PATH) study, 2013–15. (9th October 2020) - Soneji, Samir; Knutzen, Kristin E.; Gravely, Shannon; Elton‐Marshall, Tara; Sargent, James; Lambert, Elizabeth; Hilmi, Nahla; Sharma, Eva; Jackson, Kia J.; Wang, Baoguang; Robinson, Joelle; Driezen, Pete; et al.
Abstract: Background and Aims: The prevalence of hookah smoking has increased in the United States since at least 2010, especially among youth and young adults. This study assessed self‐reported reasons for hookah smoking cessation and transition to or maintenance of high‐frequency hookah smoking among current hookah smokers. Design: Separately analyzed data from the Population Assessment of Tobacco and Health (PATH) study, a longitudinal cohort study. Frequency of and reasons for hookah smoking were ascertained at wave 1 (2013–14); frequency of hookah smoking and past‐year cessation were ascertained at wave 2 (2014–15). Weighted multivariable logistic and ordinal logistic regression models were fitted to predict hookah smoking cessation and frequency of hookah smoking at wave 2, respectively, accounting for demographic and behavioral risk factors, reasons for hookah smoking and frequency of hookah smoking at wave 1. Setting: United States. Participants: A total of 693 youth and 4400 adult past‐year hookah smokers. Measurements: Self‐reported tobacco‐use patterns and associated health behaviors were measured via audio computer‐assisted self‐interviews (ACASI). Findings: At wave 1, 5.9% of youth and 7.5% of adults were past‐year hookah smokers. Among all age groups, the leading reasons for hookah smoking were enjoyment of socializing while smoking, the availability of appealing flavors and believing that it was less harmful than cigarette smoking. The odds of cessation were lower for adults who liked hookah flavors [adjusted odds ratio (aOR) = 0.40; 95% confidence interval (CI) = 0.26–0.62] compared with adults who did not like hookah flavors. The odds of transitioning to, or maintaining, monthly or more frequent hookah smoking at wave 2, compared with cessation or less than monthly smoking, were higher for adults who liked hookah flavors [adjusted proportional odds ratio (aPOR) = 2.10; 95% CI = 1.48–2.99 and enjoyed socializing while smoking hookah (aPOR = 1.82; 95% CI =1.13–2.94) compared with adults who did not like hookah flavors or socializing. Conclusion: The availability of appealing flavors, affordability and socialization while smoking hookah in the United States are associated with reduced likelihood of cessation and increased likelihood of high‐frequency hookah smoking.